Investigation of the impact of human immunodeficiency virus on cellular sumoylation - Pekbilir, Emre. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
The manifestation of Human Immunodeficiency Virus type 1 (HIV-1) infection is acquired immunodeficiency syndrome (AIDS), one of the major health problems worldwide. From the first step of infection to the end, HIV-1 customizes numerous mechanisms of the host cell to optimize its replication, thus invading the immune sys tem. Sumoylation is an essential regulator of the immune system through modulating different immune signaling pathways, including interferon signaling. SUMO proteins are the downstream effectors of interferon to antagonize bacterial and viral infections. Consecutively, various pathogens oppose sumoylation to neutralize immune responses. In this study, we investigated the interplay between host sumoylation and HIV-1. Our study demonstrates that HIV-1 diminishes cellular sumoylation by antagonizing the UBA2 protein, a subunit of the E1 SUMO-activating enzyme. HEK293 and Jurkat cells display abrogated sumoylation profiles by SUMO1 and SUMO2/3 when the HIV 1 genome is expressed. HIV-1 expression in HEK293 and Jurkat cells suppresses UBA2 protein levels as well. Therefore, HIV-1 targets cellular sumoylation by most probably antagonizing UBA2. Altogether, we demonstrated that HIV-1 impairs sumoylation, a cellular mechanism vital for immunity.
Keywords: HIV infections.; AIDS (Disease)